1995
DOI: 10.1042/bj3091021
|View full text |Cite
|
Sign up to set email alerts
|

Aggretin, a novel platelet-aggregation inducer from snake (Calloselasma rhodostoma) venom, activates phospholipase C by acting as a glycoprotein Ia/IIa agonist

Abstract: A potent platelet aggregation inducer, aggretin, was purified from Malayan-pit-viper (Calloselasma rhodostoma) venom by ionic-exchange chromatography, gel-filtration chromatography and HPLC. It is a heterodimeric protein (29 kDa) devoid of esterase, phospholipase A and thrombin-like activity. Aggretin (> 5 nM) elicited platelet aggregation with a lag period in both human platelet-rich plasma and washed platelet suspension. EDTA (5 mM), prostaglandin E1 (1 microM) and 3,4,5-trimethoxybenzoic acid 8-(diethylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
75
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 39 publications
1
75
0
Order By: Relevance
“…We also found that echicetin had a minor inhibitory effect on platelet responses to low concentrations of aggretin (data not shown). The monoclonal antibodies that had no effect on aggretin were AP-1 and 6D1 (17). Thus, the binding site for aggretin on GPIb must partly overlap with the echicetin-binding site but not with the epitopes of AP-1, 6D1, SZ-2, or Ib-23.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We also found that echicetin had a minor inhibitory effect on platelet responses to low concentrations of aggretin (data not shown). The monoclonal antibodies that had no effect on aggretin were AP-1 and 6D1 (17). Thus, the binding site for aggretin on GPIb must partly overlap with the echicetin-binding site but not with the epitopes of AP-1, 6D1, SZ-2, or Ib-23.…”
Section: Discussionmentioning
confidence: 95%
“…Several earlier studies reported proteins from the venom of C. rhodostoma that activate platelets, and it was suggested that one of these, called aggregoserpentin or aggretin, acts via ␣ 2 ␤ 1 (17). Aggretin was recently cloned, and the full amino acid sequence was established (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another example of the promiscuity of C-type lectins might be the behavior of aggretin, derived from Calloselasma rhodostoma (18). Aggretin (rhodocytin) was initially reported to bind to the integrin collagen receptor ␣ 2␤1 (19) and later reported to also bind to GPIb (18). However, more recent studies with genetically engineered murine platelets that lack ␣ 2␤1 and GPVI and were stripped of GPIb by proteolysis challenge these conclusions, showing that none of these receptors is required for platelet activation by rhodocytin (20).…”
Section: Discussionmentioning
confidence: 99%